Lussazione gleno-omerale, tecniche chirurgiche: open, artroscopiche - De Cupis, V.; Rodia, F.; Compopiano, G. (Lo Scalpello - Journal, 2018)
GLENOHUMERAL INSTABILITY, SURGICAL TECHNIQUES: OPEN, ARTHROSCOPIC The authors list the main surgical techniques, arthroscopic and open, both used for the resolution of anterior and posterior shoulder instability, which define the indications.